THE IMPLEMENTATION OF STAD–TYPE COPERATIVE LEARNING MODEL TO IMPROVE STUDENTS’ CRITICAL THINKING AND COLLABORATIVE SKILLS - Vinsensius Willy Yudhanta; Maria Melani Ika Susanti; Maria Indarti Rustamti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purposes of this study were: (1) To describe efforts to improve students' critical thinking and collaborative skills in the science subject at grade V SD Kanisius Kalasan in the even semester academic year 2020/2021; (2) To improve the students’ critical thinking skills through STAD-type cooperative learning model; (3) To improve the collaboration ability of grade V students through STAD-type cooperative learning model in science subject, especially the material of the object’s shape changes. This research was a Classroom Action Research, conducting in two cycles following the stages of planning, implementing, observing, and reflecting. Data were collected through interviews, observation, and tests. Then, the data were analyzed by using quantitative and qualitative analysis. The results showed: (1) the efforts to improve students' critical thinking and collaboration, (2) STAD-type cooperative learning model improved students' critical thinking skills; the mean score of the students’ critical thinking in the pre-cycle was 68.80; the score in cycle I was 76; and it increased to 79.36 in cycle II, (3) STAD-type cooperative learning model improved students' collaboration skills; the mean score in pre-cycle was 69.36; it increased to 84.46 in cycle I and increased to 86.25 in cycle II.